2013
DOI: 10.1002/ieam.1447
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a “Harmonized” strategy for the assessment of the HP 14 property

Abstract: In Europe, the decision whether waste is hazardous or not is based on 15 properties, among them the HP 14 property ("ecotoxic": waste that presents or may present immediate or delayed risks for 1 or more sectors of the environment). This document describes a strategy for assessing the HP 14 property, based on a combination of 2 approaches: the summation of classified compounds in the waste carried out according to the regulation on Classification, Labeling and Packaging (CLP) of substances and mixtures and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Different positions exist regarding fish tests used in waste and LLs toxicity testing. Fish tests were not included into 2013 recommendations (ethical considerations) from a 2007 EU ring test of solid waste (including waste leachate) classification, identification and basic characterization because of "animal protection reasons and the large quantity of eluate needed" (Pandard, Römbke 2013). Contrary to this position, the review on species used in the period 1983-2003 showed that fish tests were applied for evaluation of waste LLs (Férard, Ferrari 2005).…”
Section: Use Of Fish Test For Ww and Ll Toxicity Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Different positions exist regarding fish tests used in waste and LLs toxicity testing. Fish tests were not included into 2013 recommendations (ethical considerations) from a 2007 EU ring test of solid waste (including waste leachate) classification, identification and basic characterization because of "animal protection reasons and the large quantity of eluate needed" (Pandard, Römbke 2013). Contrary to this position, the review on species used in the period 1983-2003 showed that fish tests were applied for evaluation of waste LLs (Férard, Ferrari 2005).…”
Section: Use Of Fish Test For Ww and Ll Toxicity Testingmentioning
confidence: 99%
“…Thus, from an initial examination, it appears that the same biotesting principles are valid for wastes as for chemical substances (Thomas et al 2009). Two types of acute toxicity test batteries (aquatic and soil) are proposed for solid waste and LL in Germany after 2005Germany after -2007 European inter-laboratory comparison ring test (Wilke et al 2008;Moser et al 2011;Pandard, Römbke 2013). Despite the requirement to cover the traditional three trophic levels with biotest species, the aquatic tests battery for waste testing and hazard classification does not include fish (bioluminescent bacteria, algae and crustacean tests are proposed).…”
Section: Introductionmentioning
confidence: 99%
“…According to the tiered approach proposed by Pandard and Römbke (2013), the results of the aquatic tests are considered first. Out of the 23 wastes tested 13 breached the LID of 4.…”
Section: Summary: Classification Of All Test Results (Aquatic and Termentioning
confidence: 99%
“…The terrestrial test methods used in this study are briefly described in Tables 5-7. FIGURE 1: Flowchart for the assessment of the HP 14 property (Pandard and Römbke, 2013).…”
Section: Terrestrial Testsmentioning
confidence: 99%
See 1 more Smart Citation